Can Affordable Homes be Healthy? Legal Strategy, Socio-Legal Studies and Activism in Indonesia - Kouwagam, Santy (The Indonesian Journal of Socio-Legal Studies, 2022)
This article uses two Constitutional Court decisions in Indonesia to exemplify the importance of analysing legal strategies. These decisions declared a rule barring developers from building and selling tiny houses to be unconstitutional and invalid. The article shows that ‘justice’ in legal procedures still needs further definition, and that judges’ elaboration of decisions and their legal reasoning still needs improvement. The article will first discuss the cases, using Legal Strategy analysis. It will then highlight problems with the commoditisation of houses. Finally, it will argue that the problem of unhealthy and unaffordable housing in Indonesia can be resolved, by bringing together activists and researchers in a joint enterprise and tackling the issue as a collective societal project. In turn, socio-legal scholars need to keep including in-depth analysis of case law as one of the foundations of their work in law and society development.